Animating the intercultural: Revisiting Peter Brook's practice and the somatics of performance. Issue 2 (1st October 2017) - Yarrow, Ralph
My aim in this article is to frame Brook more clearly against historical parameters that affected the understanding and practice of theatre from the 1960s and to reassess to what extent his multiculturalism looks different from a twenty-first-century perspective. Brook's work up to and beyond The Mahabharata occurs in the context of post-1960 developments and attitudes to science, spirituality, aesthetics and society. During the same period, there are major developments in stage languages and embodied practices. These dimensions manifest pragmatically as a specific set of adaptations of what performers do, of the nature of the relationship between performers and receivers, and of the understanding of the nature and function of theatre and performance. The article looks at Brook's focus on the reception of his work and on what he conceived as the role of theatre in providing 'extended' experience; and at aspects of the practice of Brook and Barba with actors, which work around reduction and interruption and aim to put them in contact with the initial phases of production. It suggests that this work specifically targets the zone 'beyond' acculturation and habitus, verbal and physical. The article also revisits concerns, largely articulated by Rustom Bharucha, about the sociopolitical and economic parameters of Brook's work in India.